Scoping the implementation of recommendations from previous early generation seed studies in sub-Saharan Africa - Opie, Hellen; Akpo, Essegbemon; Desmae, Haile; Okori, Patrick; Ininda, Jane; Ojiewo, Christopher Ochieng (Wageningen University & Research, 2022)
The purpose of this report is to document and track progress on the implementation of recommendations from EGS studies that were carried out on selected countries in Eastern and Southern Africa (ESA) and West and Central Africa (WCA). The recommendations were designed to ensure a sustainable supply of EGS based on market-specific archetypes involving private, public and public-private partnerships. For the subsequent years following the conclusion and adoption of the study reports, there have been some significant achievements registered based on the country-specific recommendations from the studies. This report provides a review of the extent of implementation of the recommendations in each of the mentioned countries. The study involved a review of literature which included the country-specific EGS studies and the available literature that comprised of projects reports, recent policy documents and any other relevant available literature. Despite the list of countries in which the studies were conducted, this study only focused on the implementation of recommendations in Uganda, Kenya, Tanzania, Rwanda, Malawi, Ghana and Nigeria. Most countries have to a large extent implemented most of the recommendations from the EGS studies. A lot of emphasis was placed on addressing the creation of enabling environment aspects such as the enactment of seed acts, the plant variety protection bill and policies in Nigeria, Uganda, Ghana as well as harmonization between the national and regional seed laws. There was also emphasis towards capacity building for seed regulation and certification services through training of human resources and enabling private sector participation in seed inspection in addition to accreditation by the international bodies ISTA and OECD. PPPs were established for the root and tuber crops cassava and potatoes; and mainly hybrid and OPV maize for the cereal crops. Fingerprinting of parental lines is the most notably unimplemented for all the countries that it was recommended, but also the national establishements such as Variety Testing Center, demand forecasting frameworks and National Seed Steering committee for the case of Malawi and Tanzania respectively. It is therefore recommended that further investigation of gaps in implementation be carried to understand reasons for non-implementation.